Kapton-derived carbon as efficient terahertz absorbers. (April 2016) - Venkatachalam, S.; Bertin, D.; Ducournau, G.; Lampin, J.F.; Hourlier, D.
Abstract: The focus of this study is the preparation of carbon-based materials that satisfy the requirements of developing quasi-optic controllable absorbers for terahertz technology. These materials have been obtained from a commercially available organic polymer, Kapton ® HN polyimide, through a pyrolysis process conducted in an inert atmosphere at different temperatures. The pyrolysis of Kapton film up to 1200 °C left a black residue principally composed of graphitic-carbon with a yield of about 55%. The D.C. conductivity of materials measured at 295 K increases with increasing pyrolysis temperature. The starting organic polymer is turned from an insulator to conductor material when heat-treated at over 700 °C. Moreover, in the frequency range 220–500 GHz, the pyrolyzed materials show distinct optical properties, which have variant degrees of terahertz absorption. Kapton ® HN polyimide that is thermally converted into carbon-based materials may be used for the realization of calibrated terahertz absorbers, particularly for thermal transducers.